Flood mitigation of Kuala Lumpur: a technical review / Abdul Aziz Ahmad - Ahmad, Abdul Aziz (1983)
The Kuala Lumpur Flood Mitigation Project was implemented after the flood event of 1971 which caused a great destruction to the city of Kuala Lumpur. This project comprises of constructing new dams, that is Batu and Gombak Dams; raising of Klang Gates Dam, which was.completed in 1980; river improvement works of the three main rivers viz. Klang, Batu and Gombak Rivers; and water supply for Klang Valley and nearby communities. The study includes, the various constructions that are being carried out along the central channel section and floodway section of the three main rivers; the types of dams for the proposed Batu and Gombak.Dams, their purposes, etc. in the context of the project; and water supply which can be obtained from the existing Klang Gates Dam, new sources from the Batu and Gombak Lams and Reservoirs.and also from the Ulu Langat River development. Also include in this study is the economic analysis for the project. Datas for this project were obtained from the Drainage and Irrigation:Department (Flood Mitigation Project).